Association between objectively measured sitting time and neck–shoulder pain among blue-collar workers - Hallman, D.; Gupta, N.; Mathiassen, Svend; Holtermann, A. (Springer, 2015)
© 2015, Springer-Verlag Berlin Heidelberg. Objectives: Prolonged sitting has been suggested as a risk factor for neck–shoulder pain (NSP). Using a cross-sectional design, we investigated the extent to which objectively measured time sitting is associated with NSP among blue-collar workers. Methods: Sitting time was measured during multiple working days on male (n = 118) and female (n = 84) blue-collar workers (n = 202) using triaxial accelerometers (Actigraph) placed on the thigh and trunk. Workers were categorized into having, on average, a low, moderate or high sitting time, with mean values (SD between subjects) of 4.9 (1.0), 7.3 (0.5) and 9.6 (1.1) h in total per day. Workers rated their largest NSP intensity during the previous month on a numerical scale (0–9) and were subsequently dichotomized into a low and high NSP intensity group (ratings 0–4 and > 4, respectively). Logistic regression analyses adjusted for several individual, and work-related factors were used to investigate the association between average sitting time per day (work, leisure and total) and NSP intensity. Results: For total sitting time, workers in the high sitting category were more likely (adjusted OR 2.97, CI 1.25–7.03) to report high NSP intensity than those who sat moderately (reference category). Low sitting during work was associated with a reduced NSP intensity, but only for males (adjusted OR 0.26 CI 0.07–0.96). No significant association was found between sitting during leisure and NSP intensity. Conclusion: These findings suggest an association between sitting time, in total per day and specifically during work, and NSP intensity among blue-collar workers. We encourage studying the structure and explanation of this association further in prospective studies on larger populations.